Tennis coaching in the era of dynamic systems - Crespo, M. (Medicine and Science in Tennis, 2009)
The purpose of this article is to emphasise the importance of considering and studying tennis learning, coaching and training programs as dynamic complex systems that will help to develop a scientific paradigm of tennis alternative to the actual existing one. Tennis can be considered as an open, interdependent, dynamic, nonlinear, complex and multi-causal system. In order to try to fully understand tennis and tennis coaching it is important to use a systemic thinking approach. This approach takes into consideration the interaction of all relevant variables for the efficient functioning of the system.